Time study of Earth’s magnetic field in Colombia: Fúquene Geomagnetic Observatory (2022)
In this article the behavior over time of the Earth’s magnetic field in the municipality of Fúquene, Colombia is determined. From the historical series of magnetic field measurements over the Earth’s surface provided by the Fúquene geomagnetic observatory, which contains the historical record of 60 years of hourly measurements of the terrestrial magnetic field components, a regression analysis of the terrestrial magnetic field components as a function of time was performed. Two methods were used to remove outliers that complemented each other, the Z_score method and the Hampel filter. In the analized period since 1955 to 2015, the intensity of the terrestrial magnetic field has decreased by 14%, with a projected variation of more than 25% for the year 2055. The magnetic field intensity change rate 0.08675 [μT/year] was calculated and compared with the information reported by NOAA (National Oceanica and Atmospheric Administration) finding an excellent agreement. Besides, the ocurrence of geomagnetic storms in the data was determined, from the gradients of the horizontal component of the magnetic field during the main solar events that occurred in the study period. According to the historical behavior of the terrestrial magnetic field components, in the future we expect that the decreasing of Earth’s magnetic Field continues, which would imply a higher threat to the effects of space weather in the country, such as the generation of GICs (Geomagnetically Induced Currents) in the Colombian electricity system.